Is genetic liability to ADHD and ASD causally linked to educational attainment?. (7th June 2021) - Dardani, Christina; Riglin, Lucy; Leppert, Beate; Sanderson, Eleanor; Rai, Dheeraj; Howe, Laura D; Davey Smith, George; Tilling, Kate; Thapar, Anita; Davies, Neil M; Anderson, Emma; Stergiakouli, Evie
Abstract: Background: The association patterns of attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) with educational attainment (EA) are complex; children with ADHD and ASD are at risk of poor academic outcomes, and parental EA has been associated with risk of ADHD/ASD in the offspring. Little is known on the causal links between ADHD, ASD, EA and the potential contribution of cognitive ability. Methods: Using the latest genome-wide association studies (GWAS) summary data on ADHD, ASD and EA, we applied two-sample Mendelian randomization (MR) to assess the effects of genetic liability to ADHD and ASD on EA. Reverse direction analyses were additionally performed. Multivariable MR was performed to estimate any effects independent of cognitive ability. Results: Genetic liability to ADHD had a negative effect on EA, independently of cognitive ability (MVMR IVW: -1.7 months of education per doubling of genetic liability to ADHD; 95% CI: -2.8 to -0.7), whereas genetic liability to ASD a positive effect (MVMR IVW: 30 days per doubling of the genetic liability to ASD; 95% CI: 2 to 53). Reverse direction analyses suggested that genetic liability to higher EA had an effect on lower risk of ADHD, independently of cognitive ability (MVMR IVWOR : 0.33 per SD increase; 95% CI: 0.26 to 0.43) and increased risk of ASD (MR IVWOR : 1.51 per SD increase; 95% CI: 1.29 to 1.77), which was partly explained by cognitive ability (MVMR IVWOR per SD increase: 1.24; 95%CI: 0.96 to 1.60). Conclusions: Genetic liability to ADHD and ASD is likely to affect educational attainment, independently of underlying cognitive ability.